O impacto de tecnologias blockchain na energy cloud - Oliveira, Henrique Luís Sauer (2022)
The digitalization of electrical systems has promoted the use of intelligent technologies based on cloud computing and IoT devices, offering to consumers and prosumers a growing level of control and insight over their energy consumption and generation, allowing the emergence of cloud-based energy management systems denominated as Energy Cloud. At the same time, the use of blockchain technologies in the electrical industry has been implemented in pilot projects aiming for the decentralization of energy management in microgrid systems. In such context, this research has as objective the proposal of a theoretical architecture for the implementation of blockchain technologies in the Energy Cloud. To reach such an objective, a systematic review of the literature was performed using the PRISMA protocol, where forty-nine articles were analyzed. Based on the literature obtained, the applications and functions where blockchain technologies can be applied in the energy industry were listed. After, a theoretical architecture for the application of blockchain technologies in the Energy Cloud is proposed. Based on this architecture network policies and services are identified as well as the final user applications. Furthermore, a research instrument was developed to collect the opinion of specialists in the field of research, and an analysis of startups working in this field and proposed patents is conducted. This research is of exploratory character and qualitative approach, using qualitative modeling as method. The results of this research include a subset of descriptive text that will provide a theoretical foundation for further technology developments on the implementation of these systems on large scale, as well as lay ground for discussions and analysis from both regulatory and system integration points of view.